Biomechanical agreement between different imitation jumps and hill jumps in ski jumping - Ketterer, J.; Gollhofer, A.; Lauber, B. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Even though the take-off in ski jumping is decisive, athletes only have a very limited number of training trials on the actual ski jump to practice under real ski jump conditions. Hence, various imitation jumps aiming to mimic the hill jump are performed during daily training. These imitation jumps should therefore mimic the kinematic pattern of hill jumps appropriately. This study aimed to identify imitation jumps that resemble hill jumps regarding four performance-related biomechanical criteria: maximal vertical take-off velocity, maximal knee extension velocity, maximal forward-directed angular momentum and anterior shift of the center of mass. Therefore, a three-dimensional analysis of the take-off during six different modalities of imitation jumps as well as hill jumps for validation was carried out in nine professional ski jumpers. Imitation jumps from a rolling platform show better agreement than stationary jumps and three out of the four parameters were best resembled via an imitation jump that included ski jumping boots. Thus, non-hill take-off training should be performed with complex imitation jumps to mimic the actual ski jump. Except for the vertical take-off velocity, we could identify one imitation jump type that is not statistically different to the hill. Consequently, the individual deficiencies of the athletes can be addressed and specifically trained using the appropriate imitation jump. These information about the similarity between imitation jumps and real hill jumps are highly relevant for trainers and athletes in order to effectively design their training programs.